ANALISIS SIKAP SOSIAL PESERTA DIDIK KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 10 PONTIANAK - Dwi Maya Khairunnisa; Luhur Wicaksono; Indri Astuti (Universitas Tanjungpura, 2022)
AbstractThis study contains an analysis of the social attitudes of seventh grade students of Pontianak 10 State Junior High School. This study aims to analyze the social attitudes of students. The research method used is descriptive in the form of quantitative research. The sample in this study was 60 students of class VII, the sample was taken using random sampling, data collection was an indirect communication technique in the form of a questionnaire distributed to the entire sample as a whole. Data analysis using percentage correction. The results showed that the honesty attitude of students in the school environment with a percentage of 82% was included in the